Electrode Design Based on Porous MnO2/PPy Hybrid Nanocomposite and Its Application in Zinc-Ion Batteries - Shilin Li; Taoyun Zhou; Muzhou Liu; Qiaomei Zhao; Yi Liu; Yun Cheng; Xinyu Li (Micromachines)
The development of safe, cost-effective, and environmentally friendly energy storage systems has spurred growing interest in aqueous ZIBs. However, the poor cycling stability of cathode materials—mainly due to manganese dissolution and structural degradation—remains a major bottleneck. In this work, a porous MnO2/PPy hybrid nanocomposite is successfully synthesized via an in situ co-precipitation strategy. The conductive PPy buffer layer not only alleviates Mn dissolution and buffers volume expansion during cycling but also enhances ion/electron transport and facilitates electrolyte infiltration due to its high surface area. Electrochemical evaluation reveals that the MnO2/PPy electrode delivers excellent cycling stability, retaining 75% of its initial capacity after 1000 cycles at a current density of 1 A·g−1. Comparative performance analysis shows that MnO2/PPy exhibits superior capacity retention and rate capability, especially under high current densities and prolonged cycling. These results underscore the effectiveness of the PPy interfacial layer in improving structural integrity and electrochemical performance, offering a promising route for designing high-performance cathode materials for aqueous ZIBs.